Dampak E-Modul Terhadap Keterampilan Berpikir Kritis - Hukom, Julham (CV. SINAR HOWUHOWU, 2024)
This study aims to examine the impact of e-module use on students' critical thinking skills through a meta-analysis approach. Meta-analysis is used to integrate the results of various empirical studies published in the last five years, which specifically evaluate the effectiveness of e-modules in learning. A total of twelve studies with experimental or quasi-experimental designs were analyzed to calculate the combined effect size and test for heterogeneity between studies. The results of the analysis show that the use of e-modules has a significant impact on improving students' critical thinking skills with a combined effect size value of 0.80, which is included in the high category. This finding confirms that e-modules are an effective learning medium in fostering critical thinking skills through an interactive, independent, and contextual approach. The results of this study provide important contributions to the development of digital learning policies and the implementation of e-modules in the 21st century education system.